Cutting Performance of Diamond Coated Cemented Carbide by CVD Method - Ma, Yuping; Wang, Jinlong; Yuan, Genfu; Zhu, Shaofeng; He, Ping (Asian Journal of Chemistry, 2014)
Microcrystalline and ultrafine grain diamond films were fabricated on the cemented carbide milling tools using a bias-enhanced hot filament CVD system, respectively. The cutting performance of the uncoated and two kinds of coated milling tools has been evaluated by dry machining SiC particles reinforced aluminum matrix composites. The test results demonstrate that the cutting forces, tool wear and the surface roughness of the uncoated tools are biggest, followed by microcrystalline diamond coated tools and finally are ultrafine grain diamond coated tools. The wear life of ultrafine grain diamond coated tools is 3 times longer than the uncoated milling tools. The improved cutting performance of ultrafine grain diamond coated tools is attributed to its superior tribological properties.